If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -1x(2.5x + x) = 0 Combine like terms: 2.5x + x = 3.5x 10 + -1x(3.5x) = 0 Remove parenthesis around (3.5x) 10 + -1x * 3.5x = 0 Reorder the terms for easier multiplication: 10 + -1 * 3.5x * x = 0 Multiply -1 * 3.5 10 + -3.5x * x = 0 Multiply x * x 10 + -3.5x2 = 0 Solving 10 + -3.5x2 = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -3.5x2 = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -3.5x2 = 0 + -10 -3.5x2 = 0 + -10 Combine like terms: 0 + -10 = -10 -3.5x2 = -10 Divide each side by '-3.5'. x2 = 2.857142857 Simplifying x2 = 2.857142857 Take the square root of each side: x = {-1.690308509, 1.690308509}
| 6x-4+12=3x-4+15 | | 2x+y+10=5 | | 3-3x-3+2=5x+3 | | 3x+(-4)=2z+9 | | 4(a-3)=21 | | 8n+2-9=2n+5 | | 85+34x-23+9=-12x+15 | | 0.7*ln(200-2*x)+0.3*ln(100+0.8*x)-0.8*ln(195-0.2*x)+0.2*ln(95+0.8*x)=0 | | (7x-1)=(6x+12) | | 3(x-1)=5x-13 | | 3(0.3x-5)=7-2(0.3x+2) | | 7x+3-23=15+12-13x | | (5x-20)=(x+20) | | 18x+3y=210 | | 4(-x+7)=8 | | (7x-43)=(147-3x) | | 2(x+14)=3x+12 | | 8x-1=5x+6 | | 6x-3x=3x-9-3x | | 9x+55=7x+115 | | 4x+7-5x-2=-3x+x | | 24y-60=20y-70+2 | | 2x+24=3x+6 | | 4n/12 | | 6x+4-3x-5x=5x+2 | | 7=3=h/6 | | cos(3x)=3 | | 5-4y=3x(y-2) | | 5x+2+3=-3+2-1 | | 35x/4=6 | | 7a+3-(2a+8)=0 | | -5=3l-2 |